ANALISIS KOMPETENSI PETUGAS PROMOSI KESEHATAN PUSKESMAS DALAM PEMBERDAYAAN KADER POSYANDU KELUARGA GOTONG ROYONG DI PUSKESMAS JEREWEH KABUPATEN SUMBAWA BARAT - FIRMAN, FIRMAN; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; SUPARMAN, SUPARMAN (GANEC SWARA, 2024)
This research discusses about the Competence of Health Promotion Officers in Empowering Mutual Cooperation Families Posyandu Cadres at Jereweh Primary Health Center, West Sumbawa Regency. The objectives of this research, 1) To know the Competence of Health Promotion Officers in the aspect of empowering Family Mutual Cooperation Posyandu cadres in Jereweh Primary Health Center, West Sumbawa Regency. 2) To determine the impact of the Competency of Health Promotion Officers in the aspect of empowering Family Mutual Cooperation Posyandu cadres in the Jereweh Primary Health Center, West Sumbawa Regency. The research method used is a qualitative method, with a simple qualitative descriptive approach. Data analysis by means of data reduction, data presentation, and drawing conclusions. Data collection techniques through questionnaires, interviews, documentation. The results of the research analysis based on data obtained from 10 informants show that there are two competencies of health promotion officers in empowering posyandu cadres, namely; advocacy and empowering. Meanwhile, the impact of the competency of health promotion officers in empowering mutual cooperation families Posyandu cadres in Jereweh Primary Health Center, West Sumbawa Regency is independence, knowledge and abilities of posyandu cadres.The Conclusion of this research is the competencies of health promotion officers are advocacy and empowering. Meanwhile, the impact is independence, knowledge and ability.